1991
DOI: 10.1111/j.1467-8624.1991.tb01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Intervention and Outcome with Anxiously Attached Dyads

Abstract: Anxiously attached 12-month-olds and their mothers as assessed in the Strange Situation were randomly assigned to an intervention and a control group to test the hypothesis that infant-parent psychotherapy can improve quality of attachment and social-emotional functioning. Securely attached dyads comprised a second control group. Intervention lasted 1 year and ended when the child was 24 months. ANOVAs were used to compare the research groups at outcome. Intervention group toddlers were significantly lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(115 citation statements)
references
References 21 publications
4
108
0
2
Order By: Relevance
“…Many researchers have theorized and investigated parental attachment as a resiliency factor for traumatized children and adolescents (e.g. Cicchetti & Carlson, 1989; Lieberman, Weston, & Pawl, 1991). Among a sample of 1153 Chinese adolescents 8.5 years after Wenchuan earthquake, Tian, Wu, Wang, and Zhou (2018) found that secure parental attachment negatively predicted PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have theorized and investigated parental attachment as a resiliency factor for traumatized children and adolescents (e.g. Cicchetti & Carlson, 1989; Lieberman, Weston, & Pawl, 1991). Among a sample of 1153 Chinese adolescents 8.5 years after Wenchuan earthquake, Tian, Wu, Wang, and Zhou (2018) found that secure parental attachment negatively predicted PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…This research project assessed the effectiveness of infant-parent psychotherapy that focused on improving the infant-mother attachment bond with a group of 100 Latina mothers from Mexico and Central America, all of whom had been residents in the United States for less than 5 years ( Lieberman, Weston, & Pawl, 1991 ). Mothers were of low socioeconomic status and not acculturated to the United States.…”
Section: Preventive Intervention With High-risk Mother-infant Dyadsmentioning
confidence: 99%
“…In contrast with the large number of interventions aiming at enhancing parental sensitivity, there are few intervention studies that implicitly or explicitly address the issue of changing parental mental representations of attachment (e.g., Lieberman, Weston, & Pawl, 1991). Only one intervention evaluated its effect on parental attachment representations (Egeland, Adam, Ogawa, & Korfmacher, 1995).…”
mentioning
confidence: 99%